2018
DOI: 10.4103/1793-5482.228569
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency and methylprednisolone in treatment of lower back pain caused by facet joint syndrome: Comparison of the outcomes

Abstract: Introduction:In this trial we have discussed the outcomes of radiofrequency ablation and methylprednisolone treatment in cases diagnosed with facet syndrome; and effects of treatment modality on quality of life is evaluated by visual analogue scale and Oswestry Disability Index.Materials and Methods:This prospective, study was conducted with 100 patients with diagnosis of facet joint syndrome. Patients, benefited from diagnostic block, were separated into two groups, with 50 cases in each. In Group 1, 40 mg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Regarding the use of RF ablation, out of the 12 studies included in this analysis, 7 studies demonstrated both shortterm and long-term efficacy, [28][29][30]33,34,36,37 2 trials revealed only short-term efficacy, 31,39 whereas 3 studies showed a lack of effectiveness. 32,40,43 Four studies compared RF ablation with a sham group: in the study by Nath et al, 34 RF was associated with a significant decrease of VAS and analgesic intake at 6 months, while Leclaire 32 and van Tilburg 43 did not find any significant difference in pain scores, ODI and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the use of RF ablation, out of the 12 studies included in this analysis, 7 studies demonstrated both shortterm and long-term efficacy, [28][29][30]33,34,36,37 2 trials revealed only short-term efficacy, 31,39 whereas 3 studies showed a lack of effectiveness. 32,40,43 Four studies compared RF ablation with a sham group: in the study by Nath et al, 34 RF was associated with a significant decrease of VAS and analgesic intake at 6 months, while Leclaire 32 and van Tilburg 43 did not find any significant difference in pain scores, ODI and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up ranged from 3 months to 36 months (Table 1). Pain evaluation in these studies was performed using the VAS scale (12 studies [27][28][29][30][31][32][33][34][35][36][37][38] ), the NRS scale (5 studies [39][40][41][42][43] ), an unspecified verbal scale (1 study 44 ) and the MPI (1 study 40 ). The disability outcome was evaluated by one or more of the following scales: ODI (10 studies [30][31][32][33]35,36,38,[40][41][42], RMQ (3 studies 31,32,38 ) and an unspecified scale (1 study 44 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…But this kind of pain does not resemble sciatica as it spreads through dorsal side of the leg and reaches the feet and toes. 52 Laslett et al 53 found that a cluster of clinical signs (“Revel’s criteria”), consisting of 7 clinical signs, may be valuable in predicting the results of an initial screening ZJ block, with a sensitivity of 92% and a specificity of 80%. Although, nowadays pain produced by the LFJ has a few diagnostic scales and even though many scientists have tried to summarize the clinical features of facetogenic LBP, 51 , 53 they cannot make a diagnosis based on it.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…And hypertrophy of the facet, which is advanced deterioration of the LFJ, can mimic lumbar disc hernias with sciatica-like pain. 52 Besides, spinal synovial cysts may cause symptoms if they cause canal stenosis or nerve compression at the level of the lateral recess. 55 In Parlier-Cuau et al’s research, 56 30 patients had nerve root pain due to an LFJ synovial cyst.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation